Blood plasma lipidomic signature of epicardial fat in healthy obese women. (15th November 2014) - Scherer, Max; Montoliu, Ivan; Qanadli, Salah D.; Collino, Sebastiano; Rezzi, Serge; Kussmann, Martin; Giusti,, Vittorio; Martin, François‐Pierre J.
<x xml:space="preserve">Abstract</x> Objectives A lipidomic approach was employed in a clinically well‐defined cohort of healthy obese women to explore blood lipidome phenotype ascribed to body fat deposition, with emphasis on epicardial adipose tissue (EAT). Methods The present investigation delivered a lipidomics signature of epicardial adiposity under healthy clinical conditions using a cohort of 40 obese females (age: 25–45 years, BMI: 28–40 kg/m2) not showing any metabolic disease traits. Lipidomics analysis of blood plasma was employed in combination with in vivo quantitation of mediastinal fat depots by computerized tomography. Results All cardiac fat depots correlated to indicators of hepatic dysfunctions (ALAT and ASAT), which describe physiological connections between hepatic and cardiac steatosis. Plasma lipidomics encompassed overall levels of lipid classes, fatty acid profiles, and individual lipid species. EAT and visceral fat associated with diacylglycerols (DAG), triglycerides, and distinct phospholipid and sphingolipid species. A pattern of DAG and phosphoglycerols was specific to EAT. Conclusions Human blood plasma lipidomics appears to be a promising clinical and potentially diagnostic readout for patient stratification and monitoring. Association of blood lipidomics signature to regio‐specific mediastinal and visceral adiposity under healthy clinical conditions may help provide more biological insights into obese patient stratification for cardiovascular disease risks.